Selected factors affecting the use of the Rizal Library - Nuyda, Monnette Jennifer T. (1998)
This study seeks to provide a profile of the Rizal Library users in terms of their frequency of use, reasons for their use of the library, services and collections they utilize, their awareness of the extent of collection and services, their information-seeking behavior, their evaluation of the staff and collection and problems they encounter on their use of the library. This study also determines whether the factors sex, age, year level, course, presence of scholarship and annual family income affects the frequency of library use.